Diagnosis of extraesophageal reflux in children with chronic otitis media with effusion using Peptest - Formánek, Martin; Zeleník, Karol; Komínek, Pavel; Matoušek, Petr (International journal of pediatric otorhinolaryngology, 2015)
INTRODUCTION: The aim of the study was to investigate whether Peptest, an immunoassay used to detect pepsin, could be used to diagnose extraesophageal reflux (EER) in children with chronic otitis media with effusion (OME). The results obtained using this fast, simple and non-expensive method were compared with the results of previous studies. METHODS: Children 1-7 years old who had been diagnosed with OME and who were undergoing myringotomy with insertion of a ventilation tube were included in the prospective study. Middle ear fluid obtained during myringotomy was analyzed with Peptest to determine the presence of pepsin, and hence EER. RESULTS: Bilateral and unilateral myringotomy was performed in 15/44 (34.1%) and 29/44 (65.9%) children, respectively. Pepsin in the middle ear was detected in 14/44 (31.8%) children and in 19/59 (32.2%) middle ear specimens. Serous and mucous samples were positive for pepsin in 11/32 (34.4%) and 6/27 (22.2%) cases, respectively. Pepsin in the middle ear was detected in 3/7 children (42.9%) with bronchial asthma (p=0.662). CONCLUSIONS: Pepsin was detected in 1/3 of middle ear specimens of patients with OME. These patients probably suffer from more severe reflux and therefore would be potential candidates for antireflux therapy. However, this has to be confirmed in further studies.
Keywords: pepsin A; Children; lidé; otitis media s výpotkem; Extraesophageal reflux; prospektivní studie; Pepsin A; Infant; Female; dítě; střední ucho; Ear, Middle; gastroezofageální reflux; Humans; imunoanalýza; Gastroesophageal Reflux; Immunoassay; Middle Ear Ventilation; Prospective Studies; Gastroesophageal reflux; Otitis Media with Effusion; předškolní dítě; Chronic otitis media with effusion; Diagnostic; Child, Preschool; mužské pohlaví; Pepsin; ženské pohlaví; Male; ventilace středního ucha; Child; kojenec